Kontrol Diri dan Pembelian Impulsif Produk Kecantikan Pada Anggota Komunitas Discountfess Pengguna E-Commerce - Regina Pramudyasari, Anggun; Hari Soetjiningsih, Christiana (Jurnal Ilmiah Psyche, 2023)
The tendency of impulsive buying is the behavior of buying a product suddenly and without any planning beforehand. One of the factors that affect impulsive buying is self-control. The purpose of this study was to determine the relationship between self-control and the tendency of impulsive buying to purchase beauty products among members of the e-commerce user Discountfess community. Discountfess is a community formed on Twitter and Telegram. This community functions as a forum for people who look for a discount offer in an e-commerce shopping platform like to inform or just to show off the discounts they get. The instrument of this study used The Impulsive buying Tendency Scale (IBTS) developed by Verplanken & Herabadi to measure the scale of impulsive buying variables and The Brief Self-control Scale developed by Tangney to measure self-control variables. Participants in this study were 224 members of the Discountfess community both on Twitter and Telegram. The sampling technique used in this study was the convenience sampling technique. In order to determine the sample in this research, the researcher used a non-probability sampling technique with purposive sampling. For hypothesis data analysis testing, the researcher relies on Spearman Rho product-moment correlation supported with SPSS version 26 program as the data processing. The results showed that there was a significant negative relationship with a correlation coefficient value of 0,648 and significance value of 0.000 (p < 0,05) between self-control and impulsive buying tendencies in members of the Discountfess community who used e-commerce. Therefore, the reacherser’s hypothesis was rejected.